George and Martha rise and shine - Marshall, James. 1942- (Boston : Houghton Mifflin, 1976)
Five brief episodes about two friends, George and Martha, who happen to be hippopotamuses.
Page facing back endpaper is advertisement.
Keywords: Friendship -- Fiction; Hippopotamus -- Fiction; Short stories